PREDICTING THE REPURCHASE INTENT OF LOCAL BRAND SKINCARE CONSUMERS: Does Brand Image and Service Quality Influence? - Dewi Nur Indah Safitri; Usep Suhud; Andi Muhammad Sadat (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
The purpose of this study is to examine the effect of brand image and service quality on repurchase intention and customer satisfaction, and investigate whether customer satisfaction mediates the influence of brand image and service quality on repurchase intention. The data collection method uses a survey instrument in the form of a questionnaire. The object of this study is consumers of local brand skincare products, namely MS Glow, with samples who have purchased these products. Data analysis uses Amos to process and analyze research data. The results of the analysis show that brand image and service quality have a partial effect on repurchase intention, and that they also have a partial effect on customer satisfaction. Additionally, repurchase intention is found to mediate the relationship between brand image and service quality variables and customer satisfaction.